ANALISIS POLA PERJALANAN DAN AKTIVITAS WISATAWAN MILENIAL MANCANEGARA KE DESA PECATU, BADUNG - Maulana Pratama, Aditya; Sudana, IP.; Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 1 (2020): Jurnal IPTA (July 2020)DO - 10.24843/IPTA.2020.v08.i01.p01, 2020)
UNWTO predicts millenial tourists will become one of the biggest market shares for the tourism in the world and in Indonesia. Bali as a tourist destination and one of them is Pecatu Village, located in the area of South Kuta, Badung Regency as one of tourist destinations for millennial foreign tourists. According to this research millenials tourist are defined as the tourists group aged 16-37 years old. The purposes of this research are to find out characteristic, travel pattern and activities for the foreign millenial tourists visiting Pecatu Village. This research uses descriptive qualitative analysis, the sample was determined purposively by 100 respondent foreign millenial tourist. Data collection techniques were carried out by means of observation, questionnaires, interviews, literature studies and documentation. The results showed that Uluwatu Temple visited by 30 % of total respondents with characteristics of millenial tourists are first timer tourist with the length of stay between 2 weeks – 1 month, visiting with friends, organized their trip by themselves, using internet to get information and using motorbike as a transportation during their trip. There are 2 types of travel pattern namely single point and base trip while visiting tourist attractions and for the activites 68% them like to swimming, sunbathing, sightseeing and taking pictures.